Adverse reactions to antituberculosis drugs presenting as DRESS syndrome and acute liver failure - Carlin Ronquillo, Andrea (2022)
Drug induced liver injury (DILI) can be can be triggered by many medications including antituberculosis drugs. We present the case of a 37-year-old woman with a smear- positive pulmonary tuberculosis who started treatment with first-line antituberculosis drugs and 4 weeks later presented jaundice, somnolence and a morbilliform generalized rash with progressive neurologic deterioration which had a fatal outcome. Antituberculosis drugs can cause DILI in 2 to 28% of patients and drug reaction with eosinophilia and systemic symptoms (DRESS syndrome) in 1.2%. Acute liver failure (ALF) can occur in 35% of patients with DILI with an overall mortality of 9.7%. If the ALF is unresponsive to medical treatment, liver transplantation has shown promising results and can avoid progression of complications. DILI can be a serious medical condition in patients receiving antituberculosis drugs. If ALF develops and is unresponsive to medical treatment, liver transplantation should be considered as the treatment of choice.